The effect of attributions and failure severity on consumer complain behaviors in sharing economy - Regina Deka Sofia; Adi Zakaria Afiff; Daniel Tumpal Hamonangan Aruan (Cogent Business & Management, 2023)
Sharing economy has become a prominent business model that has been discussed in many previous studies, yet its consumer complaint behavior has not been sufficiently explored. Consumers' tolerance and overly positive review toward Partners have dominated studies in post-failure evaluation and behavior. This study was conducted to examine the effects of failure attributions, i.e. locus of causality and controllability, and severity of failure on consumers' direct and indirect complaint behavior, i.e. rating and negative word of mouth. Data were collected through a laboratory experiment with 280 participants in Indonesia. Findings revealed that at all levels of controllability and severity of failure, consumers' intentions to give low rates were higher when failures were attributed to Platforms, while there were no differences related to intentions to engage in negative word of mouth. Results also showed the interaction of attribution of controllability and severity of failure toward consumers' intention to give Partners low rates. These results contributed to research related to consumer complaint behavior in sharing economy, particularly negative word of mouth that still needed to be discussed adequately.
Keywords: 650; attribution; complaint behavior; digital platforms; negative word of mouth; severity of failure; sharing economy